Effect of Gd3+ doping on structural, morphological, optical, dielectric, and nonlinear optical properties of high-quality PbI2 thin films for optoelectronic applications. Issue 16 (28th August 2019) - Shkir, Mohd.; AlFaify, Salem
Abstract: Abstract : Herein, we present the fabrication and characterization of Gd:PbI2 thin films from low-cost material using a cost-effective spin-coating technique by taking the Gd content as 1.0, 2.0, and 3.0 wt% in PbI2 . Single-phase and good crystallinity films oriented along the c -axis were confirmed by X-ray diffraction and FT-Raman spectroscopy. Size of crystallites increased with Gd concentration and was estimated to be in the range of 16–32 nm. Determination of morphology and size of grains (50–103 nm), and elemental confirmation were carried out by SEM/EDX analysis. Optical transparency of fabricated films was found to be in the range of 72–92%. The energy gap is reduced from 2.31 to 2.05 eV; this makes Gd:PbI2 films highly applicable in solar cells. The stable value of refractive index is estimated to be in the range of 1.85–2.3. Dielectric constant was observed to be reduced with doping and in the range of 2.5–35, and ac conductivity was also reduced by doping; however, both were enhanced with frequency. The values of χ (1), χ (3), and n (2) are found to be in the range of 0.15 to 2.5, 8 × 10 −14 to 6.5 × 10 −9, and 5 × 10 −12 to 4 × 10 −8, respectively.